Analisis Kesiapan Implementasi Rekam Medis Elektronik Menggunakan Instrumen CAFP (California Academy of Family Physicians) di Puskesmas Kartasura - Hapsari, Dyah Ayu; Andriani, Rika; Igiany, Prita Devy (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2023)
Ministry of Health Indonesia Regulation No. 24 of 2022 about Medical Records confirms that all health service facilities are required to maintain Electronic Medical Records (EMR) no later than December 31, 2023. The Kartasura Health Center is one of the health centers in Sukoharjo Regency which has not yet implemented EMR. The CAFP instrument is used for evaluating First Level Health Facilities in transitioning to EMR so as to improve service quality and workflow efficiency. The purpose of this study is to determine the readiness of implementing EMR on management capacity, finance & budgeting, operations, technology, and organizational alignment. This research is descriptive quantitative research. The population is 108 people with a sample of 9 people selected by stratified random sampling. Collecting data using interviews and documentation studies. The results showed that management capacity was in range II with a value of 9.3; financial capacity and budget are in range III with a value of 5.2; operational capacity is in range III with a value of 3.5; technology capacity is in range III with a value of 9.4; and organizational alignment capacity is in range II with a value of 17.3. Overall readiness for EMR implementation at the Kartasura Health Center is in range II. Increasing financial & budgetary, operational, and technological capacity needs to be improved with the IT team, EMR training, and EMR outreach to all potential users.